Indirect spectrophotometric determination of Cephalexin and paracetamol by Cu-NTA complex in aqueous solution - Thabit Al-Ghabsha; Theiaa Al-Sabha; Amal Saeed (College of Education for Pure Sciences, 2005)
A spectrophotometric method has been described for the determination of cephalexin and paracetamol by their reaction with Cu-NTA complex in aqueous solution leading to increase the complex absorbance at Xmax=832 nra from which the excess absorbance is measured. Beer's law is obeyed over the concentration range of 0.05-3.20 ppt for cephalexin and 0.20-2.75 mg/ml for paracetamol. The average recoveries are 97.13% and 98.03% for the above drugs respectively, and precision (RSD) is found to be better than 4% for both drugs. The method has been applied successfully for determination of the above drugs in some of their pharmaceutical preparations. The results obtained are in agreement with their certified values and also with standard addition procedure.